The Stress Hormones Adreno Cortico Tropin, Cortisol, Catecholamines and Pregnancy Exercises for Childbirth - Ayu Resky Mustafa; Anita Febrianti Purba; Anisa Wardati; Wulan Ramadhanti; Bayumi (Postgraduate, University of Mataram, 2023)
During pregnancy there are safe changes both physically and psychologically. Mothers who experience anxiety and stress, the signal travels through the Hypothalamo-Pituitary-Adrenal (HPA) which can cause the release of stress hormones including Adreno Cortico Tropin Hormone (ACTH), cortisol and catecholamines. The release of stress hormones in pregnant women results in systemic vasoconstriction, including placental vasa utero constriction which causes impaired blood flow in the uterus, so that oxygen transport into the myometrium is disrupted and results in weak uterine muscle contractions. This study aims to determine the effectiveness of pregnant gymnastics has a relationship with anxiety levels as a prenatal service in reducing anxiety facing first labour. The type of research used in this study is the Quasi Experiment method. The type of research used in this study is experimental research, which is a research procedure carried out by providing treatment / intervention on research subjects, with the aim of assessing the effect of a treatment on the independent variable on the dependent variable. The results of the study indicate that pregnant gymnastics as a prenatal service is effective in reducing anxiety facing the first childbirth, this can be seen from the results before and after the treatment and prenatal service of pregnant gymnastics.